Estimation of the global solar radiation using RadEst 3.00 software at Tribhuvan International Airport, Nepal - Dawadi, Nabin; Manoj Kumar Shrestha,; Khatri, Kisan; Poudyal, Khem Narayan; Karki, Indra Bahadur; Tiwari , Babu Ram (BIBECHANA, 2026)
Daily global solar radiation (GSR) at Tribhuvan International Airport in Kathmandu (27.69° N, 85.35° E; elevation 1338 m) was estimated by using the RadEst 3.0 software, employing meteorological data from 2014 and 2015. The study investigates both seasonal and monthly GSR variations and evaluates overall radiation levels. RadEst 3.0 implements four empirical models: Campbell and Donatelli (CD), Bristow and Campbell (BC), the Modular DCBB model, and Donatelli and Bellocchi (DB), each relying on the diurnal temperature range (the difference in daily peak and low air temperatures) to estimate GSR. The radiation is calculated by multiplying atmospheric transmissivity with extraterrestrial radiation, and the software optimizes model parameters to derive the necessary coefficients. Estimated GSR values and the resulting coefficients were validated against observed data using statistical indicators. Of the models assessed, the Modular DCBB model delivered the most reliable results for the year 2015 with a root mean square error (RMSE) of 2.94 MJ/m², coefficient of determination (R²) of 0.53, residual mass coefficient (CRM) of 0.00, and mean bias error (MBE) of 2.29 MJ/m². These findings identify the Modular DCBB model as the most accurate for the study location and suggest its parameterization is well suited for GSR estimation in regions with similar climatic conditions across Nepal.